Value of Strategic Planning to Ensure the Sustainability of the Business Structures of Education and Science: Experience and Problems - A. A. Galushkin (Путеводитель предпринимателя)
This article presents an analysis of the transformation of the realities ofbusiness organizations and science educators in an effort to improve their competitiveness.